2020
DOI: 10.1002/ps.5869
|View full text |Cite
|
Sign up to set email alerts
|

20‐Hydroxyecdysone regulates the prophenoloxidase cascade to immunize Metarhizium anisopliae in Locusta migratoria

Abstract: BACKGROUNDPPO (prophenoloxidase) cascade plays an important role in resisting invasion of entomogenous fungus. The 20‐hydroxyecdysone (20E) exerts potent effect on the innate immunity in many insects. However, whether 20E controls the PPO cascade system against fungi and the regulatory mechanism in insects remains unclear.RESULTSIn this study, both the proteome and transcriptome of Locusta migratoria were determined followed by the induction of 20E. Pattern recognition receptor GNBP‐2 (Gram‐negative binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…During the onset of metamorphosis, 20E initiates various early gene expression cascades and induces the formation of the pupal cuticle in order to regulate the insect’s developmental transitions ( Dong et al., 2003 ; King-Jones et al., 2005 ; Yamanaka et al., 2013 ). Previous studies have demonstrated that 20E modulates the cellular and humoral innate immunity of insects ( Flatt et al., 2008 ; Tian et al., 2010 ; Sun et al, 2016 ) by priming the production of various effector genes, including cecropins ( Reynolds et al., 2020 ; Nunes et al., 2020 ) and PPOs ( Han et al, 2020 ; Reynolds et al., 2020 ). The results of Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…During the onset of metamorphosis, 20E initiates various early gene expression cascades and induces the formation of the pupal cuticle in order to regulate the insect’s developmental transitions ( Dong et al., 2003 ; King-Jones et al., 2005 ; Yamanaka et al., 2013 ). Previous studies have demonstrated that 20E modulates the cellular and humoral innate immunity of insects ( Flatt et al., 2008 ; Tian et al., 2010 ; Sun et al, 2016 ) by priming the production of various effector genes, including cecropins ( Reynolds et al., 2020 ; Nunes et al., 2020 ) and PPOs ( Han et al, 2020 ; Reynolds et al., 2020 ). The results of Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was reversed by the addition of exogenous ecdysone in the insect blood meal, suggesting that the hormone regulates the IMD pathway. Likewise, it has been suggested that the IMD pathway is under hormonal regulation in Drosophila (Flatt et al, 2008;Rus et al, 2013;Zheng et al, 2018) and in Locusta migratoria (Han et al, 2020;Han et al, 2017), in which ecdysone activates the expression of genes encoding a peptidoglycan recognition protein LC (PGRP-LC). Genomic and transcriptomic analyses highlighted the presence of some, but not all, genes encoding components of the IMD pathway in R. prolixus (Nishide et al, 2019;Ribeiro et al, 2014;Zumaya-Estrada et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its role in insect development and reproduction, ecdysone is also associated with the regulation of the immune system in various species (Ahmed et al, 1999;Dimarcq et al, 1997;Han et al, 2020;Han et al, 2017;Ma et al, 2019;Meister and Richards, 1996;Tian et al, 2010). In Drosophila melanogaster, ecdysone has a role in the insect's humoral response; both in vivo and in vitro treatments with ecdysone increase levels of expression of antimicrobial peptides (AMPs) (Flatt et al, 2008;Rus et al, 2013;Zhang and Palli, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The total PO activity of desert locusts gradually decreased with M. acridum infection [ 119 ]. Except for the PPO activation system, PPO transcription expression is responsive to infection by Metarhizium and is regulated by hormones and two genes likewise [ 87 , 120 ]. 20E further promoted the expression of GNBP2 to increase PPO expression in the fat body of locusts infected with M. anisopliae [ 120 ].…”
Section: The Late-phase Interactionmentioning
confidence: 99%
“…Except for the PPO activation system, PPO transcription expression is responsive to infection by Metarhizium and is regulated by hormones and two genes likewise [ 87 , 120 ]. 20E further promoted the expression of GNBP2 to increase PPO expression in the fat body of locusts infected with M. anisopliae [ 120 ]. Decreased expression of IAP boosted PO activity during infection by M. acridum .…”
Section: The Late-phase Interactionmentioning
confidence: 99%